MODEL PEMBELAJARAN ROLE PLAYING PADA MATA PELAJARAN PS-EKONOMI MATERI POKOK MANUSIA SEBAGAI MAKHLUK SOSIAL DAN EKONOMI - Kardoyo, -; Wahyuningtyas, Esti Mumpuni (Dinamika Pendidikan, 2009)
Student activity in economic learning class VII state junior high school Bantarbolang is low and the result study of economic couldnÃ¢â‚¬â„¢t reach study completing. Study completing reach 51.16% and class mean only 6.53. All student activity are managed if learning be motivated to reach some goals. In the way to reach the objectives, student be faced in active condition to play a role and discussion that guided by teacher. The object of this research to find out how the learning process in Economic concentration with topic people as a social human being and economic class VII state senior high school 3 Bantarbolang Pemalang region. In the year 2006/2007 using learning model of role playing. The result study show there is increasing score reach in last cycle II is 7.81 with study completing classically 86.05%. And the result study of last cycle II reach classically completing 77.74%, from the result of this research be expected that teacher of economic subject in class VII use learning model of role playing in topic people as a social human being and economic. Adding facilities to complement learning process and give motivating and information about the topic that being learned. Keywords :The implementation of learning model of role playing Ã‚Â